Neurobehavioral Initiation and Motivation Problems After Acquired Brain Injury - Palmisano, Simona; Fasotti, Luciano; Bertens, Dirk (Frontiers in Neurology, 2020)
Abstract Motivation is a primary and permanent source of human behavior and adaptation.Motivational deficits, along with deficiencies in initiation, frequently occur in individuals with Acquired Brain Injury (ABI). These neurobehavioral problems are associated with consequences at participation level: patients are reluctant to engage in rehabilitation and their subsequent social reintegration is often at risk. The same problems may also become a heavy burden for the families of individuals with ABI. In the present paper we will critically review both the current definitions and the instruments used to measure motivational disorders following ABI. We will also describe the neural systems underlying motivation and its impairments. What emerges is the need to develop specific rehabilitative treatments, still absent at the moment, with the ultimate aim of ensuring a better quality of life for both the patients and their proxies. To be edited.